poem of my youth - Sawel Awuni (Vernacular: New Connections in Language, Literature, & Culture, 2024)
This document contains five poems: Napoleon Bonaparte, Work, Anger, Peace, O My Africa, and Love. The first poem depicts the French king who ended the revolution and ruled the country. The following three poems express the challenges faced by West African countries. The final poem beautifully portrays the essence of love.
Keywords: Napoleon Bonaparte; Work; Anger; Peace; O My Africa; and Love